Whole genome sequencing of Lacticaseibacillus casei KACC92338 strain with strong antioxidant activity, reveals genes and gene clusters of probiotic and antimicrobial potential - Kandasamy, Sujatha; Lee, Kil-Ho; Yoo, Jayeon; Yun, Jeonghee; Kang, Han Byul; Kim, Ji Eun; Oh, Mi-Hwa; Ham, Jun-Sang (Frontiers in Microbiology, 2024)
Lacticaseibacillus casei KACC92338 was originally isolated from Korean raw milk. The antioxidant activities and protective effect in vitro of this strain were evaluated extensively. The results showed that KACC92338 can tolerate hydrogen peroxide up to 2 mM and cell-free supernatant (CFS) had higher scavenging rates for DPPH, hydroxyl radical, reducing power, and iron chelating activities with 95.61 ± 1.59%, 34.10 ± 1.93%, 2.220 ± 0.82 and 81.06 ± 1.06%, respectively. Meanwhile, the CFS showed a protective effect on yeast cells against 10 mM hydrogen peroxide with a survival rate of 76.05 ± 5.65%. To explore the probiotic potential of KACC92338, whole genome assembly and gene clusters with probiotic properties were further analyzed. The genome size was 3,050,901 bp with a 47.96% GC ratio, and 63 contigs. The genome contains 3,048 genes composed of 2,981 coding sequences and 67 RNAs (including 57 tRNAs +9 rRNAs +1 tmRNA). Average Nucleotide Identity and genome-based taxonomy showed that the KACC92338 genome had close similarity with L. casei strains with 96% ANI. Functional annotation by EggNOG and KEGG revealed the presence of numerous genes putatively involved in carbohydrate- and amino acid-transport and metabolism, genetic information processing, and signaling and cellular processes. Additionally, several genes conferring probiotic characteristics such as tolerance to stress, heat, cold, acid, bile salts, oxidative stress, immunomodulation, and adhesion to intestinal epithelium were identified. Notably absent were acquired antibiotic resistance genes, virulence, and pathogenic factors, that prove KACC92338 is a safe strain. Besides, the defense mechanisms of KACC92338 include six prophage regions and three clustered regularly interspaced short palindromic repeat (CRISPR) arrays as acquired immune systems against mobile elements. Further, the BAGEL4 database determined antimicrobial bacteriocin clusters of class IIb: sakacin-P, Enterolysin_A, sactipeptides, and Enterocin X, which suggests the strain could exhibit a wide range of antimicrobial functions. Together, these findings show that the L. casei KACC92338 strain can be a potential probiotic candidate in producing functional fermented foods-, health care- and skin care products- with antioxidant properties. However, a few more mechanistic studies are necessary on the safety assurance and potential application of the strain as a probiotic agent.